Lysine supplementation of commercial fishmeal‐free diet in hybrid striped bass Morone chrysops x M. saxatilis affects expression of growth‐related genes. (13th April 2015) - Childress, C.J.; Fuller, S.A.; Rawles, S.D.; Beck, B.H.; Gaylord, T.G.; Barrows, F.T.; McEntire, M.E.
Abstract: Our recent results in hybrid striped bass (HSB) concluded that ideal protein theory accurately predicts first‐limiting amino acids in commercial diet formulations if accurate amino acid availability data are used and that appropriate levels of supplemental lysine are needed to improve fish performance from fishmeal‐free diets. Our goal in this study was to elucidate how dietary lysine supplementation of a commercial fishmeal‐free diet influences the expression of two genes, myostatin and myogenin, controlling myogenesis in differentially growing groups of HSB. Real‐time RT‐PCR results in HSB suggest that the levels of lysine added to the diet (17.8, 35.1, 51.0 g kg −1 of diet) has an impact on myogenin relative to the basal unsupplemented diet, but no effect on myostatin . Moreover, our data further suggest that the amount of dietary lysine supplementation influenced the ratio of myostatin/myogenin expression in HSB and that this pattern mimicked that of most of the growth, composition of growth and nutrient retention data from our previous study and may therefore be a useful marker for selecting fish for improved growth performance.